La perrita que le encantaban las tortillas : un libro de Dieguito = The dog who loved tortillas : a Little Diego book - Saenz, Benjamin Alire; Garcia, Geronimo (New York : Scholastic Inc., 2009)
When Gabriela and her brother Little Diego get a puppy named Sofie, they fight over who she belongs to, but when Sofie gets very sick they find the answer
Bilingual = Bilingue
Grades 1-3.